2017
DOI: 10.1044/2016_jslhr-l-15-0329
|View full text |Cite
|
Sign up to set email alerts
|

Current Methods of Evaluating Speech-Language Outcomes for Preschoolers With Communication Disorders: A Scoping Review Using the ICF-CY

Abstract: The review revealed a dearth of measures in the pediatric speech-language literature that address Participation-based outcomes. The authors strongly advocate for the use of Participation-based outcome measures to detect meaningful change in the lives of children and families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 62 publications
2
43
0
2
Order By: Relevance
“…The revised International Classification of Functioning, Disability, and Health (ICF) shifts thinking from a biomedical model to a biopsychosocial model, that includes consideration of the body functions and structure, activity, participation, the environmental and personal factors [43]. Application of this model in research and practice encourages a focus on the family, functional use of skills and the child's participation in real world contexts [44,45]. Definition and measurement of the family environment in pediatric rehabilitation [46] and the personal factors component of the ICF has been a challenge [47].…”
Section: Discussionmentioning
confidence: 99%
“…The revised International Classification of Functioning, Disability, and Health (ICF) shifts thinking from a biomedical model to a biopsychosocial model, that includes consideration of the body functions and structure, activity, participation, the environmental and personal factors [43]. Application of this model in research and practice encourages a focus on the family, functional use of skills and the child's participation in real world contexts [44,45]. Definition and measurement of the family environment in pediatric rehabilitation [46] and the personal factors component of the ICF has been a challenge [47].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there has been insufficient consideration of how best to measure objectively functional limitations within the overall picture of Quality of life in children with DLD 801 childhood language assessment and diagnosis. A recent scoping review concluded there was currently a lack of tools for measuring functional limitations in the paediatric speech and language field (Cunningham et al 2017). Furthermore, we are not aware of any studies that have quantified the contribution of language abilities across the developmental spectrum to QoL in children more generally.…”
Section: Biopsychosocial Model Of Disabilitymentioning
confidence: 99%
“…A recent scoping review concluded there was currently a lack of tools for measuring functional limitations in the paediatric speech and language field (Cunningham et al . ). Furthermore, we are not aware of any studies that have quantified the contribution of language abilities across the developmental spectrum to QoL in children more generally.…”
Section: Introductionmentioning
confidence: 97%
“…speech sounds) and Activities (e.g. receptive language skills) components; very little research has explored outcomes related to the Participation component; and little has been published on the development of communicative participation skills – how children use their communication to engage in life . We believe these are meaningful and practical outcomes, and are the outcomes important to families …”
mentioning
confidence: 99%